(untitled) (Kindle, 2022)
Cancer development is known by summative action of multiple events occurring in single cell. It can be characterized by three stages: Initiation, promotion, and progression. ROS is involved in all these phases. The effect of oxidative stress at a certain phase of carcinogenesis is directly proportionate to the type and the reactivity of radicals involved. Initiation results when a normal cell sustains a DNA mutation that, when preceded by a round of DNA production, leads to fixation of the mutation, producing an initiated cell. Initiation of malignancy by ROS is supported by presence of oxidative DNA modifications in cancer tissues. The promotion stage is known by clonal expansion of initiated cells, by stimulation of cell proliferation and/or inhibition of apoptosis. Oxidative stress is strongly involved in this phase. ROS can induce expansion of mutated cell clones by temporarily modulating the genes which are associated with proliferation or cell death and by regulating function of certain transcription factors which control cell growth and oncogenesis. A low level of oxidative stress can induce cell division in promotion stage, and therefore promotes tumor growth. This implies that ROS synthesis during this stage is the main mechanism of ROS‑related tumor promotion. ROS also has role in the last stage of carcinogenesis; progression. Antioxidants are substances or agents that scavenge reactive oxygen metabolites, block their production, or increase endogenous antioxidants capabilities. High intake of antioxidants was correlated with a reduced risk of head and neck squamous cell carcinoma among smokers, drinkers, and those with both smoking and drinking habits. Recent evaluations have shown that they are abundant in fruits and vegetables as well as in other foods such as nuts, grains, some meats, poultry, and fish.